An Ethnobotanical Survey of Medicinal Plants and Associated Traditional Knowledge Among the Tribal Communities of Jharkhand, India - Sinha , Deepa; Kumar, Veermani; Patra , Kamal Kant; Mishra , Asha (American Journal of Botany and Bioengineering, 2025)
This ethnobotanical study documents the traditional medicinal practices of tribal communities in Jharkhand through a survey of 50 informants, comprising 30 males and 20 females aged 35–85 years (mean age: 62). A majority (75%) were above 60 years, with 60% serving as traditional healers, underscoring the centrality of elders in safeguarding indigenous knowledge. Informants reported 45 medicinal plant species belonging to 32 families and 41 genera. The Lamiaceae, Fabaceae, and Asteraceae families were most represented. Leaves emerged as the dominant plant part (32.5%), followed by roots (24%) and bark (15%), highlighting both therapeutic versatility and potential ecological risks from unsustainable root and bark harvesting. Medicinal plants were most frequently used for gastrointestinal disorders (22.5%), dermatological conditions (20%), and respiratory problems (15%), reflecting community health priorities shaped by local living conditions. High Informant Consensus Factor (ICF) values for gastrointestinal (0.90) and respiratory ailments (0.88) indicate strong cultural consensus, while the low ICF for snakebite (0.36) reveals fragmented knowledge limited to specialists. Quantitative indices identified Neem (Azadirachta indica) and Tulsi (Ocimum sanctum) as culturally significant species, with the highest Relative Frequency of Citation (0.96 and 0.90) and Use Values (2.4 and 1.8), confirming their versatility in treating multiple ailments. The findings emphasize the urgency of documenting orally transmitted knowledge, which is concentrated among a few elderly healers, while also highlighting sustainability concerns. This research contributes to preserving cultural heritage, guiding conservation strategies, and offering leads for pharmacological exploration, ensuring that Jharkhand’s ethnomedicinal wisdom informs both local healthcare and broader scientific inquiry.